Media Sosial Dan Tingkat Religiusitas Pengaruhnya Terhadap Aktualisasi Nilai-Nilai Moderasi Beragama Pada Generasi-Z - Yulyani, Rani Dewi; Rifiananda, Muhammad Attila (MOMENTUM : Jurnal Sosial dan Keagamaan, 2025)
The intensity of Generation Z in accessing digital platforms and increasing religious awareness can serve as an effective means of conveying messages of religious moderation. A survey conducted among students in Serang City revealed that 88.1% of respondents use the Internet as a reference source for information and academic purposes. The research method employed in this study is a quantitative descriptive method, using a survey conducted on 97 Generation Z respondents categorized as active university students in Serang City. The results of the survey for the variables of social media, religiosity levels, and religious moderation can be stated, based on the index numbers obtained, that all variables fall into the good category. Furthermore, the study's findings also explain that the proposed research hypothesis can be accepted, showing that both social media and religiosity levels have a positive and significant impact on religious moderation among Generation Z.